Hubungan Antara Self Compassion Dengan Alienasi Pada Siswa SMA Negeri 11 Pekanbaru - Juliya Rahayu, Riska (Journal of Islamic and Contemporary Psychology, 2021)
Student education does not always run smoothly, partly because of the influence of rejection of being excluded from school and peers, rejection leads to alienation. Alienation is a feeling condition in which someone feels not part of anything that no one cares about by staying away from something. This study aims to determine the relation between self compassion and alienation in students senior high school 11 pekanbaru. The research subjects is120 students of senior high school 11 Pekanbaru. The sampling technique in this research was using proportionate stratified random sampling technique. The data collection process uses two scales, the Alienation scale is arranged by haldun (2018) which amounts to 15 items and self compassion scale is arranged by Hasanah and Hidayati (2016) which amounts to 24 items.While the statistical analysis data used in this research is the peason product moment. The result of data analysis showed a correlation coefficient of rxy is -0,186 with p is 0,042 (p<0,05). It can be concluded that there is a negative and significant the relation between Self Compassion and Alienation in students senior high school 11 Pekanbaru. Where the correlation value is negative, it’s mean more high self compassion, the more low in students, the opposite more low self compassion, the more high alienation.